Al sur del sueño : Argentina Chile. - Museo Nacional de Bellas Artes, Buenos Aires (Buenos Aires : Museo Nacional de Bellas Artes, 1994)
Fazzolari, Fernando ; Frigerio, Ismael ; Garreaud, Eduardo ; Garretón, Sebastián ; Israel, Patricia ; Lecuona, Juan ; Medici, Eduardo ; Medici, Héctor ; Nigro, Miguel Angel ; Wells, Ulrich
Al sur del sueño : Argentina Chile, Museo Nacional de Bellas Artes, Buenos Aires, Julio 1994
boek